2002
DOI: 10.1161/hc0902.104599
|View full text |Cite
|
Sign up to set email alerts
|

Change in Diastolic Left Ventricular Filling After One Year of Antihypertensive Treatment

Abstract: Background-It is well established that hypertensive patients with left ventricular (LV) hypertrophy have impaired diastolic filling. However, the impact of antihypertensive treatment and LV mass reduction on LV diastolic filling remains unclear. Methods and Results-Echocardiograms were recorded in 728 hypertensive patients with ECG-verified LV hypertrophy (Cornell voltage-duration or Sokolow-Lyon) at baseline and after 1 year of blinded treatment with either losartan or atenolol-based regimen. Systolic and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(38 citation statements)
references
References 40 publications
(36 reference statements)
1
35
0
2
Order By: Relevance
“…LV diastolic dysfunction associated with exercise intolerance in patients with hypertensive response to exercise but no resting hypertension was similar in degree to that of patients with both hypertensive response to exercise and resting hypertension. Consistent with previous reports, we observed a correlation between arterial hypertension and impaired LV diastolic performance in patients with hypertension (4,5). In increased systolic arterial pressure, there is an upward shift in the LV diastolic pressure-volume ratio, resulting in an increase in left atrial pressure indicated by an increased E/E′ (24), and slow LV relaxation, as indicated by a decreased E′.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LV diastolic dysfunction associated with exercise intolerance in patients with hypertensive response to exercise but no resting hypertension was similar in degree to that of patients with both hypertensive response to exercise and resting hypertension. Consistent with previous reports, we observed a correlation between arterial hypertension and impaired LV diastolic performance in patients with hypertension (4,5). In increased systolic arterial pressure, there is an upward shift in the LV diastolic pressure-volume ratio, resulting in an increase in left atrial pressure indicated by an increased E/E′ (24), and slow LV relaxation, as indicated by a decreased E′.…”
Section: Discussionsupporting
confidence: 91%
“…Increase in systolic blood pressure (SBP) causes slow myocardial relaxation, left ventricular (LV) hypertrophy and potentially adverse effects on passive chamber stiffness (4,5). Thus, many patients with long-standing hypertension have Doppler echocardiographic evidence of impaired diastolic function, which may limit exercise tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Regression of LVH has been shown to improve systolic function, and reduce the risk of ventricular arrhythmias and atrial fibrillation [2022]. Moreover, in patients with and without kidney failure, regression of LVH is associated with decreased all-cause mortality, rendering this a valid surrogate health outcome in this population [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to show a significant improvement in diastolic dysfunction from a grade of 3.4 to 1.2 after 1 year of NHD with an improvement in overall LV filling pressures. While regression of diastolic dysfunction has been associated with LVH regression in prior studies, it is not known whether this leads to improved survival or a reduction in cardiovascular events [20, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…The regression of cardiac hypertrophy and fibrosis is accompanied by an improvement of LV diastolic function, with increased rate of active relaxation and decreased passive chamber stiffness [51,52]. The two phenomena, hypertrophy regression and diastolic improvement, are partly independent from each other.…”
Section: Effects Of the Raas Blockade On Hypertensive Heart Diseasementioning
confidence: 99%